The flower of the gods: form and frame in Araweté singing (Amazonia) - Heurich, Guilherme Orlandini (2017)
In this paper, I analise the refrains or choruses of the Araweté's oñ?ñã me'e songs. I use the araweté concept of “people-carrier” to associate the refrains with other aesthetic forms such as the “tocaia” complex among other Tupi-guarani groups. Using data gathered during 14 months of fieldwork, I trace connections between body ornaments, hunting and shamanic “tocaias”, rattles, shamans, and the refrains. I argue that the refrains “function” not only as a framing device in the lines of the songs but also as a plastic frame sustained by rhythm and movement.